Haemoglobin Profiles of University Students Participating in Routine Medical Examinations, 2009-2011 - Pitkin, Fabian (Archives of Clinical and Biomedical Research, 2017)
Introduction: Haemoglobin estimation is one of the most frequently investigated laboratory tests as it is the primary predictor of anaemia. Anaemia is a major public health concern in places all around the world as it is known to adversely impact energy levels. Aims and objectives of this study were to evaluate the prevalence of anaemia based on haemoglobin measurement among University students who participated in routine medical examinations 2009- 2011. Method: Two hundred and seventy-two cases were included in a convenient sampling. Blood was collected in the standard K3EDTA purple top tubes. Samples were thoroughly mixed and haemoglobin estimation was done using the HemoQue Haemoglobin System. Commercial controls were run with each batch. Results: Commercial controls results showed 1.1559 % coefficient of variation. Mean age and haemoglobin concentration of all students were 23.011 ± 2.919 years (range 17-36), and 13.209 ± 1.356 g/dl (range 7.6 - 19.7), respectively. The mean haemoglobin for males and females was 14.19 and 12.51 respectively, t = 9.297(p =0.0001) Anaemia prevalence was lower in males than females (19.4%; n = 113 vs 32.7%; n = 159 respectively. Conclusions: The anaemia prevalence is higher in female than in males, approximately almost twice as high. At the institution where the study was conducted, emphasis is placed on quality nutrition, a likely factor in stemming the prevalence of the more common dietary related anaemias. Nevertheless, more laboratory evaluations will be needed to determine the specific cause of anaemia in the student population whose haemoglobin falls below the WHO age and gender specific cut off points.